2020
DOI: 10.1002/jmv.26449
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin is a neuraminidase inhibitor of influenza viruses

Abstract: Influenza A virus (IAV) causes great morbidity and mortality worldwide every year. However, there are only a limited number of drugs clinically available against IAV infection. Further, emergence of drug‐resistant strains can render those drugs ineffective. Thus there is an unmet medical need to develop new anti‐influenza agents. In this study, we show that punicalagin from plants possesses strong anti‐influenza activity with a low micromolar IC50 value in tissue culture. Using a battery of bioassays such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…For example, punicalagin decreases yeast plasma membrane ergosterol causing severe ultrastructural changes on Cryptococcus gattii and Candida albicans ( Silva et al, 2020 ). Otherwise, ellagic acid inhibits sialidase of Trypanosoma congolense ( Aminu et al, 2017 ) and neuraminidase on influenza A virus ( Li et al, 2021 ). Reports about Giardia indicate that oseltamivir, a viral neuraminidase (sialidase) inhibitor, affects GM1 ganglioside, a major constituent of lipid rafts, and disassembled these microdomains ( De Chatterjee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, punicalagin decreases yeast plasma membrane ergosterol causing severe ultrastructural changes on Cryptococcus gattii and Candida albicans ( Silva et al, 2020 ). Otherwise, ellagic acid inhibits sialidase of Trypanosoma congolense ( Aminu et al, 2017 ) and neuraminidase on influenza A virus ( Li et al, 2021 ). Reports about Giardia indicate that oseltamivir, a viral neuraminidase (sialidase) inhibitor, affects GM1 ganglioside, a major constituent of lipid rafts, and disassembled these microdomains ( De Chatterjee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following virus replication, NA removes sialic acid from the surface of infected cells to release the newly synthesized virus for infection of more cells ( Gamblin and Skehel, 2010 ). Punicalagin, an ellagitannin with strong anti-influenza activity, has demonstrated its primary mechanism of action by acting on the NA-mediated viral release, in addition to its inhibitory activity on the replication of influenza A and B viruses, including oseltamivir-resistant virus (NA/H274Y) ( Li et al, 2021 ). A study on extracts of fifty medicinal plants from the tropical rainforests of Borneo against the H1N1 and H3N1 viruses revealed that all extracts acted through the inhibition of viral NA and only four extracts were found to inhibit hemagglutination.…”
Section: Plants With Antimicrobial Activity and Their Mechanisms Of A...mentioning
confidence: 99%
“…Some plants that are not included in traditional Chinese medicine, such as pomegranate and ginger, can also exert antiviral activity. Punicalagin, a broad-spectrum influenza inhibitor derived from pomegranate, has an inhibitory effect on different subtypes of influenza virus by inhibiting the NA protein activity of influenza virus and then blocking the release of progeny virus [102]. It is worth noting that Punicalagin also had a significant inhibitory effect on oseltamivir-resistant strains [102].…”
Section: Development and Effects Of Plant Extracts On Influenza Virusmentioning
confidence: 99%
“…Punicalagin, a broad-spectrum influenza inhibitor derived from pomegranate, has an inhibitory effect on different subtypes of influenza virus by inhibiting the NA protein activity of influenza virus and then blocking the release of progeny virus [102]. It is worth noting that Punicalagin also had a significant inhibitory effect on oseltamivir-resistant strains [102]. In addition, the ginger extract Gingerenone A acts as a dual inhibitor of JAK2 and p70S6 kinase (S6K1) to inhibit influenza virus replication by inhibiting JAK2 activity and interfering with viral assembly [103].…”
Section: Development and Effects Of Plant Extracts On Influenza Virusmentioning
confidence: 99%